If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(n+1)=49
We move all terms to the left:
6(n+1)-(49)=0
We multiply parentheses
6n+6-49=0
We add all the numbers together, and all the variables
6n-43=0
We move all terms containing n to the left, all other terms to the right
6n=43
n=43/6
n=7+1/6
| (4x+8)+(3x+22)=180 | | -6(x+4)=30(x-2) | | 8q=3q-5 | | 8q=3q−5 | | 8.5x+8.5x+x+x=43 | | -8k+1=-5-10k | | 4(-4x+3)=44 | | 3+5c=2(c+8) | | a^2/5-29/25-30/25=0 | | 8/5=169/x | | x+7/13=2 | | z-17=30 | | -8k+1=-5−10k | | (4x+30)+(3x+66)=180 | | -6x2-6x+12=0 | | 72.75+20x=70 | | 180=x+(4x-7)+(3x-5) | | -3x+4x=12+3x | | 10/7=n/21 | | 5+24y+11=y+9y-26 | | X+12=6y | | 5.1x-6.6=2.4-0.9x | | 3x+13+x+20+7x-15=180 | | 2{4x-6(x-2)}-4=5x+2 | | 3x(x+1=10+2x | | -45=-3(-4n+3) | | 2x+52=3x+35 | | 4-5(2x-1)=10-3-2x | | 48-3x=42-9x | | -3.1-2x=5.1 | | 2y-85=685 | | X/5-x-4/10=9/10 |